Two-photon double ionization of the helium atom by ultrashort pulses - Palacios, A; Horner, D A; Rescigno, T N; McCurdy, C W (Journal of physics. B, Atomic, molecular, and optical physics, 2010)
Two-photon double ionization of the helium atom was the subject of early experiments at FLASH and will be the subject of future benchmark measurements of the associated electron angular and energy distributions. As the photon energy of a single femtosecond pulse is raised from the threshold for two-photon double ionization at 39.5 eV to beyond the sequential ionization threshold at 54.4 eV, the electron ejection dynamics change from the highly correlated motion associated with nonsequential absorption to the much less correlated sequential ionization process. The signatures of both processes have been predicted in accurate ab initio calculations of the joint angular and energy distributions of the electrons, and those predictions contain some surprises. The dominant terms that contribute to sequential ionization make their presence apparent several eV below that threshold. In two-colour pump--probe experiments with short pulses whose central frequencies cause the sequential ionization process to dominate, a two-electron interference pattern emerges that depends on the pulse delay and the spin state of the atom.